2007
DOI: 10.1159/000099145
|View full text |Cite
|
Sign up to set email alerts
|

Open-Heart Surgery in Patients with Liver Cirrhosis: Indications, Risk Factors, and Clinical Outcomes

Abstract: Background: Because of recent advances in cardiopulmonary bypass (CPB) surgery, there are broadened indications to approach patients with a high operative risk. Meanwhile, there is an increasing number of patients with severe liver dysfunction subjected to open-heart surgery. This retrospective study was designed to evaluate the operative indications and clinical outcomes in patients with liver cirrhosis (LC) undergoing open-heart surgery. In addition, determinants influencing their prognosis were assessed. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 47 publications
5
24
1
2
Order By: Relevance
“…Therefore, only limited data are available to assess specific indicators that identify and stratify those patients who are at high risk for open-heart surgery. Certainly, several reports have shown that open-heart surgery with the use of CPB in patients with liver cirrhosis is associated with adverse clinical outcome and an increased risk for morbidity and mortality, particularly in patients with CTP classes B and C. While the mortality rates of patients in CTP class A were reported to be 10% and less, mortality in CTP class B patients ranges between 0% and 80% and goes up to 100% for CTP class C patients [7][8][9][10][11][12]. These results demonstrate that CTP classes B and C are a heterogeneous group of patients; a more precise definition of the risk in liver cirrhosis patients is thus warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, only limited data are available to assess specific indicators that identify and stratify those patients who are at high risk for open-heart surgery. Certainly, several reports have shown that open-heart surgery with the use of CPB in patients with liver cirrhosis is associated with adverse clinical outcome and an increased risk for morbidity and mortality, particularly in patients with CTP classes B and C. While the mortality rates of patients in CTP class A were reported to be 10% and less, mortality in CTP class B patients ranges between 0% and 80% and goes up to 100% for CTP class C patients [7][8][9][10][11][12]. These results demonstrate that CTP classes B and C are a heterogeneous group of patients; a more precise definition of the risk in liver cirrhosis patients is thus warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, liver disease has not been addressed as an independent preoperative risk factor by any of the routinely used and established cardiac surgical risk score models (e.g., European system for cardiac operative risk evaluation (EuroSCORE); except for Pons et al) [3][4][5][6]. Recent evidence only comes from several small studies showing highly increased shortand long-term mortality rates for those patients, who undergo cardiac surgery having end-stage liver disease with liver cirrhosis of Child-Turcotte-Pugh (CTP) classification B or C [7][8][9][10][11][12]. On the other hand, over the past several decades, liver transplantation has emerged as a viable treatment option for patients with end-stage liver disease [13], and the prevalence of concomitant cardiac disease in these patients often carry cardiac risk factors, such as ageing, obesity, diabetes mellitus, hypertension and hyperlipidaemia [14].…”
Section: Introductionmentioning
confidence: 99%
“…In patients undergoing cardiac surgery, the risk of mortality or complications may be high when a cardiopulmonary bypass is performed on patients with chronic liver disease [223] . In general, the mortality of cirrhotic patients with C-P grade A is low, but that of patients exhibiting C-P grade B for a long period and that of all patients with C-P grade C is high, especially when open heart surgery is performed.…”
Section: Risk Of Surgery In Patients With Liver Diseasesmentioning
confidence: 99%
“…Moreover, the principal causes of death in Child B patients 4/6 were hemorrhage and infection, while the cause of death in Child A and C patients (1/17 and 1/1, respectively) were infection. In this study, platelet count was not different in survivors vs. nonsurvivors, and other parameters related to coagulation and hemostasis were not explored in relation to survival or to frequency of complications [100]. In another study reporting on outcomes after open-heart surgery in 12 patients with cirrhosis, 6 of whom were in Child A and 6 in Child B classes, major complications including hemorrhage and hepatic decompensation were associated with platelet count, while mortality (5/12) was associated with bleeding complications in 3 cases [101].…”
Section: Bleeding Risk Associated With Surgerymentioning
confidence: 80%